Comparison of Clinical Outcomes between Plastic Stent and Novel Lumen-apposing Metal Stent for Endoscopic Ultrasound-Guided Drainage of Peripancreatic Fluid Collections - Ho Cheol Shin; Chang Min Cho; Min Kyu Jung; Seong Jae Yeo (Korean Society of Gastrointestinal Endoscopy, 2019)
Background/Aims Endoscopic ultrasound (EUS)-guided transmural drainage for peripancreatic fluid collections (PFCs) has gained wide acceptance as a nonsurgical intervention. Although a lumen-apposing metal stent (LAMS) was recently introduced, there are few data comparing the clinical outcomes between LAMS and plastic stent (PS) drainage. Methods Endoscopy databases of all patients who had undergone EUS-guided drainage for PFCs were searched and the clinical outcomes of EUS-guided drainage according to stent-type used were compared. Results A total of 27 patients (median age, 56 years) with PFCs underwent EUS-guided transmural drainage between January 2011 and December 2017. Of these, 17 underwent PS placement and 10 underwent LAMS placement. There was no significant difference in the technical success rate between the 2 groups (94.1% vs. 100%, p=1.0). Procedure time was shorter in the LAMS group compared to that in the PS group (10.6±2.5 min vs. 21.4±9.5 min, p=0.002). Among subjects with clinical success, recurrence of PFC after stent removal occurred in 5 of 12 patients with PS and 4 of 10 with LAMS, without statistical difference (41.7% vs. 40.0%, p=1.0). Conclusions Although our study showed similar clinical outcomes for LAMS and PS, further prospective trials are required to validate the superiority of LAMS.